33rd Joint Propulsion Conference and Exhibit 1997
DOI: 10.2514/6.1997-3189
|View full text |Cite
|
Sign up to set email alerts
|

Emergency flight control using only engine thrust and lateral center-of-gravity offset - A first look

Abstract: Normally, the damage that results in a total loss of the primary flight controls of a jet transport airplane, including all engines on one side, would be catastrophic.In response, NASA Dryden has conceived an emergency flight control system that uses only the thrust of a wing-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The development which follows is similar in spirit to Alwi & Edwards [16] but is different in detail because of the model reference setting. Using (4) and (5), it can be shown that (1) can be written aṡ…”
Section: A Model Reference Sliding Mode Control Allocation Schemementioning
confidence: 99%
“…The development which follows is similar in spirit to Alwi & Edwards [16] but is different in detail because of the model reference setting. Using (4) and (5), it can be shown that (1) can be written aṡ…”
Section: A Model Reference Sliding Mode Control Allocation Schemementioning
confidence: 99%
“…PCA is a special case of MMST, where the only anticipated fault is total hydraulics failure and only the engines can be used for control. There have been some successful flight tests with PCA on a F-15 and an MD-11 in the beginning of the 1990's [32,33].…”
Section: Multiple Model Controlmentioning
confidence: 99%
“…The design procedure starts by defining the tracking errors as 32) where α * are the intermediate control laws to be defined. The dynamics of z 1 satisfẏ…”
Section: Control Designmentioning
confidence: 99%
“…After the possibility of control using only the engine throttles was demonstrated by the Sioux City accident (see Chapter 1), and following a recommendation from the National Transportation Safety Board of America, the PCA problem was taken up by the NASA Dryden Flight Research Center [16,17] in order to provide a backup in case of total hydraulic failure. PCA is a specific instance of a multi-model approach where the fault model is identical to the nominal one, but in which all control surfaces are free floating.…”
Section: Propulsion Controlled Aircraft (Pca)mentioning
confidence: 99%